Pengaruh Carbon Emission Disclosure Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Kinerja Lingkungan Sebagai Variabel Moderasi - Tanti Hardianti; Susi Dwi Mulyani (Peneliti.net, 2023)
This study aims to empirically determine the effect of Carbon Emission Disclosure (CED) and firm size on firm value with environmental performance as a moderating variable. This study uses a quantitative approach using secondary data. The sample was selected using a purposive sampling technique with a population of non-financial companies registered on the IDX from 2019 - 2021. This study uses multiple linear regression techniques to test the hypothesis using the SPSS program. The results of the study show that carbon emission disclosure has a positive effect on the firm's value. The results of this study also reveal that environmental performance has a significant positive effect on firm value, so it can be concluded that PROPER can be used as a company signal to increase firm value.